PENCURIAN BERKUALIFIKASI YANG DILAKUKAN OLEH ANAK - Rezky Ridhoyanti Rhamani; Ahkam Jayadi; ST Nurjannah (Alauddin Law Development Journal, 2019)
The application of criminal sanctions with a decision Number 63/pid.sus-anak/2018/pn-mks and Law Number11 of 2012 on child defendants who have fulfilled the elements of action in article 363 paragraph 1 sub 3 of the Criminal Code, criminal acts of theft the condition is burdensome and in a state of physical and psychological health so that according to the judge the defendant can conclusively account for his actions. In accordance with the facts of the trial both from the testimonies of the witnesses and the testimony of the defendant who acknowledged his mistake and the evidence before the court so that legally and convincingly the defendant was guilty, in addition to the verdict, the judge considered mitigating and burdening the accused child.